Decoding Gen-Z Voter Reactions to Political Hoaxes: a Deep Dive Into the 2024 Indonesian Presidential Election - Hayat, Nahrul; M, Maemunah; Hidayati, Sari (Jurnal Review Politik, 2025)
This study explores how Gen-Z voters in South Sulawesi, Indonesia, process and respond to political hoaxes during the 2024 presidential election. Using qualitative exploratory methods, data from 323 respondents in Makassar and Parepare were collected through focus group discussions (FGDs), interviews, and online questionnaires. The analysis, guided by the Elaboration Likelihood Model and Reception Theory, reveals that while Gen-Z voters generally exhibit rational affirmative behaviors, their responses to political hoaxes are shaped by political bias and motivations. Notably, 87% of respondents admitted to sharing misinformation about opposing politicians, while 46% were likely to dismiss hoaxes targeting candidates they support. This selective processing of political information highlights the critical need for digital literacy initiatives to equip Gen-Z with skills for critically assessing information. Strengthening digital literacy can empower this generation to make informed decisions, thereby fostering a transparent, inclusive, and resilient democratic process. The study underscores the importance of education in reducing Gen-Z's vulnerability to misinformation and calls for targeted programs to address confirmation bias. Future research should expand on these findings by examining rural Gen-Z voters to gain a broader understanding of voter behavior across diverse demographics in Indonesia.